Exposure to Electronic Waterpipes Increases the Risk of Occlusive Cardiovascular Disease in C57BL/6J Mice - Precious O. Badejo MS; Shelby S. Umphres MS; Hamdy E.A. Ali PhD; Ahmed B. Alarabi PhD; Shahnaz Qadri PhD; Fatima Z. Alshbool PharmD, PhD; Fadi T. Khasawneh PhD (SAGE Publishing, 2024)
Introduction It is well documented that cardiovascular disease (CVD) is the leading cause of death in the US and worldwide, with smoking being the most preventable cause. Additionally, most smokers die from thrombotic-based diseases, in which platelets play a major role. To this end, because of the proven harm of smoking, several novel tobacco products such as electronic(e)-waterpipe have been gaining popularity among different sectors of the population, partly due to their "false" safety claims. While many investigators have focused on the negative health effects of traditional cigarettes and e-cigarettes on the cardiovascular system, virtually little or nothing is known about e-waterpipes, which we investigated herein. Methods and Materials To investigate their occlusive CVD effects, we employed a whole-body mouse exposure model of e-waterpipe vape/smoke and exposed C57BL/6J male mice (starting at 7 weeks of age) for 1 month, with the controls exposed to clean air. Exposures took place seven times a week, according to the well-known Beirut protocol, which has been employed in many studies, as it mimics real-life waterpipe exposure scenarios; specifically, 171 puffs of 530 ml volume of the e-liquid at 2.6 s puff duration and 17 s puff interval. Results The e-waterpipe exposed mice had shortened bleeding and occlusion times, when compared to the clean air controls, indicating a prothrombotic phenotype. As for the mechanism underlying this phenotype, we found that e-waterpipe exposed platelets exhibited enhanced agonist-triggered aggregation and dense granule secretion. Also, flow cytometry analysis of surface markers of platelet activation showed that both P-selectin and integrin GPIIb-IIIa activation were enhanced in the e-waterpipe exposed platelets, relative to the controls. Finally, platelet spreading and Akt phosphorylation were also more pronounced in the exposed mice. Conclusion We document that e-waterpipe exposure does exert untoward effects in the context of thrombosis-based CVD, in part, via promoting platelet hyperreactivity.